2022
DOI: 10.1177/15330338221133690
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical, and Oncological Outcomes of non-Alcohol Drinking and non-Smoking Laryngeal Squamous Cell Carcinoma Patients: A Distinct Entity

Abstract: Purpose: To explore the discrepancy in clinicopathological and prognostic features between smoking and alcohol drinking (SA) and non-smoking and non-alcohol drinking (NSNA) patients with laryngeal squamous cell carcinoma (LSCC). Methods: This retrospective study including 1735 patients with LSCC was conducted from January 2005 to December 2010, which were categorized into 4 groups, NSNA group, smoking only group, alcohol-drinking only group, and SA group. We compared overall survival (OS) and disease-free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This information requires attention to consider revising the traditional screening paradigm. Another study, performed by Huang et al also demonstrated that non-smoking and non-alcohol-drinking female patients are more likely to represent LSCC cases and more at the earlier stage of the disease [ 37 ]. Moreover, the results of the study suggested that non-smoking and non-alcohol-drinking LSCC patients not only have the same rate of disease recurrence as smoking and alcohol-drinking patients, but they also have a comparable disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This information requires attention to consider revising the traditional screening paradigm. Another study, performed by Huang et al also demonstrated that non-smoking and non-alcohol-drinking female patients are more likely to represent LSCC cases and more at the earlier stage of the disease [ 37 ]. Moreover, the results of the study suggested that non-smoking and non-alcohol-drinking LSCC patients not only have the same rate of disease recurrence as smoking and alcohol-drinking patients, but they also have a comparable disease outcome.…”
Section: Discussionmentioning
confidence: 99%